An Arabidopsis Zinc Finger Protein Increases Abiotic Stress Tolerance by Regulating Sodium and Potassium Homeostasis, Reactive Oxygen Species Scavenging and Osmotic Potential - Zang, Dandan; Li, Hongyan; Xu, Hongyun; Zhang, Wenhui; Zhang, Yiming; Shi, Xinxin; Wang, Yucheng (Frontiers in Plant Science, 2016)
Plant zinc finger proteins (ZFPs) comprise a large protein family and they mainly involve in abiotic stress tolerance. Although Arabidopsis RING/FYVE/PHD ZFP (At5g62460; AtRZFP) is found to bind to zinc, whether it is involved in abiotic stress tolerance is unknown. In the present study, we characterized the roles of AtRZFP in response to abiotic stresses. The expression of AtRZFP was induced significantly by salt and osmotic stress. AtRZFP positively mediates tolerance to salt and osmotic stress. Additionally, compared with wild-type Arabidopsis plants, plants overexpressing AtRZFP showed reduced reactive oxygen species accumulation, enhanced superoxide dismutase and peroxidase activity, increased soluble sugars and proline contents, reduced K+ loss, decreased Na+ accumulation, stomatal aperture and the water loss rate. Conversely, AtRZFP knockout plants displayed the opposite physiological changes when exposed to salt or osmotic stress conditions. These data suggested that AtRZFP enhances salt and osmotic tolerance through a series of physiological processes, including enhanced reactive oxygen species scavenging, maintaining Na+ and K+ homeostasis, controlling the stomatal aperture to reduce the water loss rate, and accumulating soluble sugars and proline to adjust the osmotic potential.